An explicit expression for strain in geomembrane uplifted by wind. Issue 6 (December 2009) - Giroud, J.P.
Abstract : ABSTRACT: The design of geomembrane liners exposed to the risk of uplift by wind involves an implicit equation for the geomembrane strain in the case where the geomembrane has a linear tension–strain curve. Solving this equation by iterations is tedious and hinders the work of design engineers. This technical note presents an approximate solution to the implicit equation. The geomembrane strain calculated using the proposed approximate equation is very accurate for the entire range of geomembrane strains typically considered in design (error less than 0.01% of the strain value for usual strains). Therefore, the proposed equation can be considered as a quasi-exact solution.